Functional Properties of Physically Pretreated Kidney Bean and Mung Bean Flours and Their Performance in Microencapsulation of a Carotenoid-Rich Oil - Locali-Pereira, Adilson Roberto; Kubo, Mirian Tiaki Kaneiwa; Fuzetti, Caroline Gregoli; Nicoletti, Vânia Regina (Frontiers in Sustainable Food Systems, 2022)
Microencapsulation can improve protection for compounds that degrade easily, such as β-carotene that is present in large amounts in buriti oil (Mauritia flexuosa). Encapsulating matrices are mainly composed of proteins and polysaccharides, which are often combined to improve their performance as a protective barrier. Beans, such as dark red kidney beans (Phaseolus vulgaris) and mung beans (Vigna radiata), are excellent protein sources that contain significant amounts of the essential amino acids. Bean flours are low in fat and naturally provide a blend of high-quality protein and carbohydrates that may stabilize lipophilic compounds for subsequent spray-drying. Whole bean flours, rather than refined individual biopolymers, may represent more sustainable alternative wall materials for microencapsulate bioactive compounds. This work aimed to evaluate the use of flours produced from red kidney beans and mung beans, which have been submitted to different physical pretreatments, as wall materials for microencapsulation of buriti oil by spray-drying. Different bean treatments were evaluated: untreated (control), soaked in water for 24 h, and soaked in water for 24 h followed by boiling for 30 min. The flours' proximate composition was not affected by the treatments (p < 0.05), showing similar values of carbohydrate (63.8–67.9%), protein (19.2–24.6%), and lipid (1.2–1.9%) contents. Both bean species had the water absorption capacity (WAC) increased by boiling, while the oil absorption capacity (OAC) was not altered by the treatments. Flours produced with raw or soaked beans showed emulsion activity (EA) and emulsion stability (ES) greater than 70%. Raw bean flours also showed better foaming properties, which may be indicative of higher levels of antinutritional factors. The soaked bean flours showed the best results for both type of beans, especially with regard to emulsifying properties, and were selected as wall materials for buriti oil microencapsulation. Different ratios of flour and maltodextrin were used to produce oil-in-water emulsions that were then spray-dried. Buriti oil microcapsules showed good physicochemical properties, with moisture around 3%, aw <0.3, and hygroscopicity around 5%. The carotenoid encapsulation efficiency ranged from 68.2 to 77.9%. Bean flours showed to function as a sustainable and nutrient-rich alternative wall material for microencapsulation.